EFEKTIVITAS PEMANFAATAN QUIZWHIZZER DALAM EVALUASI PEMBELAJARAN SEJARAH TERHADAP MINAT BELAJAR SISWA KELAS XI - Fadila Gita Cahayani; Romadi (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
Research specifically examining the effectiveness of Quizwhizzer as an assessment tool for history education in relation to students’ interest in learning is still relatively scarce; therefore, this study is necessary to address this gap. Low student interest in history learning remains a common problem in schools, including at TEUKU UMAR SEMARANG High School. This is due to the fact that the learning and evaluation processes are still dominated by conventional media that are unengaging, and the use of interactive digital media has not been optimized. One innovative solution that can be offered to address this issue is the use of Quizwhizzer. The implementation of Quizwhizzer in history learning assessment provides a more memorable learning experience through interactive game-based assessment. This study aims to determine the effectiveness of using Quizwhizzer as an assessment tool for history learning on the learning interest of 11th-grade students. The research method used is a quasi-experimental approach with a Nonequivalent Control Group design. The study subjects involved two groups: an experimental class and a control class, each with 30 students, resulting in a total sample size of 60. Data collection utilized a Likert-scale questionnaire that had undergone validity and reliability testing, supplemented by observational and interview data. The research procedure included administering a pretest, instruction according to the treatment, and a posttest. Data analysis was conducted using the Shapiro-Wilk normality test, the Levene homogeneity test, as well as the Independent Samples t-Test and Welch’s t-Test. Based on the analysis, the research results indicate that there is a significant difference in the effects between the experimental and control groups, with the experimental class outperforming the control class. These findings are reinforced by observational results showing increased enthusiasm, engagement, and interest among students through the use of the Quizwhizzer platform during instruction. Thus, it is concluded that the use of Quizwhizzer as an assessment tool for history instruction has proven effective in enhancing students’ interest in learning and serves as an innovative approach to history education at the high school level. ABSTRAK Penelitian yang menguji efektivitas Quizwhizzer sebagai media evaluasi pembelajaran sejarah terhadap minat belajar peserta didik secara spesifik masih relatif sedikit sehingga penelitian ini perlu dilakukan untuk melengkapi kesenjangan tersebut. Rendahnya minat belajar peserta didik terhadap pembelajaran sejarah menjadi permasalahan yang masih sering ditemukan di sekolah salah satunya di SMA TEUKU UMAR SEMARANG. Hal itu disebabkan karena proses pembelajaran dan evaluasi masih didominasi media konvensional yang kurang menarik serta belum optimal pemanfaatan media digital interaktif. Salah satu soluasi inovatif yang dapat ditawarkan untuk mengatasi masalah tersebut adalah pemanfaatan media Quizwhizzer. Penerapan media Quizwhizzer dalam evaluasi pembelajaran sejarah memberikan pengalaman belajar yang lebih berkesan melalui media evaluasi berbasis game interaktif. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan media Quizwhizzer sebagai media evaluasi pembelajaran sejarah terhadap minat belajar peserta didik kelas XI. Metode penelitian yang digunakan adalah pendekatan quasi-eksperiment desain Nonequivalent Control Group. Subjek penelitian melibatkan dua kelompok yaitu kelas eksperimen dan kelas kontrol dengan masing-masing 30 peserta didik sehingga total sampling sebanyak 60. Pengumpulan data menggunakan instrumen angket skala Likert yang telah melalui validitas dan reliabilitas serta didukung oleh data pelengkap observasi dan wawancara. Untuk prosedur penelitian meliputi pemberian pretest, pembelajaran sesuai perlakuan, posttest. Analisis data dilakukan melalui uji normalitas Shapiro-Wilk, uji homogenitas Levene, serta uji Independent Sample t-Test dan Welch’s t-Test. Berdasarkan analisis hasil penelitian menunjukkan bahwa terdapat perbedaan pengaruh yang signifikan antara kelompok eksperimen dan kontrol, dengan hasil lebih unggul kelas eksperimen dibandingkan kelas kontrol. Temuan ini diperkuat oleh hasil observasi yang menunjukkan peningkatan antusiasme, keterlibatan, dan minat peserta didik melalui penerapan media Quizwhizze selama pembelajaran. Dengan demikian, disimpulkan bahwa pemanfaatanQuizwhizzer sebagai media evaluasi pembelajaran sejarah terbukti efektif dalam meningkatkan minat belajar peserta didik dan menjadi inovai pembelajaran sejarah di jenjang sekolah menengah atas.